Pemberdayaan Perempuan melalui Inovasi Teknologi IoT dan Energi Terbarukan dalam Pengelolaan Bank Sampah - Nur, Yohani Setiya Rafika; Tanjung, Nia Annisa Ferani; Ginting, Melinda Br.; Sulaeman, Gilang; Al Faiz, M. Hanif (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Waste banks are a form of circular economy initiative that increase the added value of inorganic waste while empowering local communities. However, their operations often face limitations such as inadequate production facilities, high energy costs, and manual record-keeping systems. This community service program aimed to strengthen the capacity of the “Sampah Sahabatku” Waste Bank in Muntang Village through the application of appropriate technology based on solar panels and IoT sensors, as well as by enhancing women’s roles in management. The implementation methods included situation analysis, solar panel installation, technical and managerial training, mentoring, and evaluation using pre-test and post-test assessments. The results showed that solar panels successfully reduced electricity costs and supported the operation of plastic and paper shredding machines, while IoT sensor integration improved the accuracy of record-keeping. The average knowledge level of participants increased by +58% after training. The community’s response was highly positive, reflected in improved technical skills and greater confidence among women in waste bank management. In conclusion, the combination of appropriate technology and renewable energy has strengthened the independence, efficiency, and sustainability of community-based waste banks.ABSTRAKBank sampah merupakan salah satu instrumen ekonomi sirkular yang dapat meningkatkan nilai tambah sampah anorganik sekaligus memberdayakan masyarakat. Namun, pengelolaan bank sampah sering menghadapi keterbatasan sarana produksi, tingginya biaya energi, dan sistem pencatatan yang masih manual. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas Bank Sampah “Sampah Sahabatku” di Desa Muntang melalui penerapan teknologi tepat guna berbasis panel surya dan sensor IoT, serta penguatan peran perempuan dalam pengelolaan. Metode pelaksanaan meliputi analisis situasi, pemasangan panel surya, pelatihan teknis dan manajerial, pendampingan, serta evaluasi melalui pre-test dan post-test. Hasil kegiatan menunjukkan bahwa panel surya mampu mengurangi biaya listrik dan mendukung operasional mesin pencacah plastik maupun kertas, sementara integrasi sensor IoT meningkatkan akurasi pencatatan. Nilai rata-rata pemahaman mitra meningkat sebesar +58% setelah pelatihan. Respon mitra juga positif, ditandai dengan meningkatnya keterampilan teknis dan kepercayaan diri perempuan dalam pengelolaan bank sampah. Kesimpulannya, kombinasi teknologi tepat guna dan energi terbarukan mampu memperkuat kemandirian, efisiensi, serta keberlanjutan bank sampah berbasis komunitas.